A SYSTEMATIC REVIEW OF THE RISK OF MOTOR VEHICLE COLLISION AND DEMENTIA. (11th November 2018) - Carr, D; Rapoport, M
Abstract: Guidelines that physicians use to assess fitness to drive for dementia are limited in their currency, applicability, and rigor of development. We performed a systematic review to determine the risk of motor vehicle collisions or driving impairment caused by dementia. Seven literature databases retrieved 12, 860 search results: we included nine studies in this analysis, involving 378 participants with dementia and 416 healthy controls. We found medium to large effects of dementia on driving abilities in six of the seven recent studies that examined driving impairment. Persons with dementia were more likely to fail a road test than healthy controls (RR: 10.77, 95% CI: 3.00–38.62, z=3.65, p<0.001), with no significant heterogeneity (χ2=1.50, p=0.68, I2=0%). Even mild stages of dementia place patients at substantially higher risk of failing a performance-based road test and of demonstrating impaired driving abilities on the road.